A large chromosomal inversion shapes gene expression in seaweed flies (Coelopa frigida). Issue 6 (7th October 2021) - Berdan, Emma L.; Mérot, Claire; Pavia, Henrik; Johannesson, Kerstin; Wellenreuther, Maren; Butlin, Roger K.
Abstract: Inversions often underlie complex adaptive traits, but the genic targets inside them are largely unknown. Gene expression profiling provides a powerful way to link inversions with their phenotypic consequences. We examined the effects of the Cf‐Inv(1) inversion in the seaweed fly Coelopa frigida on gene expression variation across sexes and life stages. Our analyses revealed that Cf‐Inv(1) shapes global expression patterns, most likely via linked variation, but the extent of this effect is variable, with much stronger effects in adults than larvae. Furthermore, within adults, both common as well as sex‐specific patterns were found. The vast majority of these differentially expressed genes mapped to Cf‐Inv(1) . However, genes that were differentially expressed in a single context (i.e., in males, females, or larvae) were more likely to be located outside of Cf‐Inv(1) . By combining our findings with genomic scans for environmentally associated SNPs, we were able to pinpoint candidate variants in the inversion that may underlie mechanistic pathways that determine phenotypes. Together the results of this study, combined with previous findings, support the notion that the polymorphic Cf‐Inv(1) inversion in this species is a major factor shaping both coding and regulatory variation resulting in highly complex adaptive effects.